2022
DOI: 10.1097/xcs.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medicaid Expansion on Pancreatic Cancer: An Examination of Sociodemographic Disparity in 1-Year Survival

Abstract: BACKGROUND: This study examined the effect of Medicaid expansion on 1-year survival of pancreatic cancer for nonelderly adults. We further evaluated whether sociodemographic and county characteristics alter the association of Medicaid expansion and 1-year survival. STUDY DESIGN: We obtained data from the Surveillance Epidemiology and End-Results dataset on individuals diagnosed with pancreatic cancer from 2007 to 2015. A Difference-in-Differences model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…While most of the growth was observed in expansion states—12 million newly insured—nonexpansion states also saw over 2 million Americans enroll in the program (Uberoi et al, 2016 ). Medicaid expansion is associated with greater access to health care overall, greater access to opioid treatment, lower cardiovascular mortality, a decline in overall mortality rates, and significant increases in preventative care, cancer survival rate, outpatient care utilization, and improved health care quality (Khatana et al, 2019 ; Meinhofer & Witman, 2018 ; Miller et al, 2019 ; Miller & Wherry, 2019 ; Mobley et al, 2022 ; Sommers et al, 2016 ; Wen et al, 2017 ). Multiple studies have found overall improvements in insurance coverage due to the implementation of the ACA, especially in reducing racial and ethnic disparities in access to health insurance (Buchmueller et al, 2016 ; Mazurenko et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While most of the growth was observed in expansion states—12 million newly insured—nonexpansion states also saw over 2 million Americans enroll in the program (Uberoi et al, 2016 ). Medicaid expansion is associated with greater access to health care overall, greater access to opioid treatment, lower cardiovascular mortality, a decline in overall mortality rates, and significant increases in preventative care, cancer survival rate, outpatient care utilization, and improved health care quality (Khatana et al, 2019 ; Meinhofer & Witman, 2018 ; Miller et al, 2019 ; Miller & Wherry, 2019 ; Mobley et al, 2022 ; Sommers et al, 2016 ; Wen et al, 2017 ). Multiple studies have found overall improvements in insurance coverage due to the implementation of the ACA, especially in reducing racial and ethnic disparities in access to health insurance (Buchmueller et al, 2016 ; Mazurenko et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent study demonstrated an increased probability of 1-year survival for patients diagnosed with and treated for pancreatic adenocarcinoma in Medicaid expansion states. 3 However, socioeconomic and racial/ethnic disparities persisted. The present study was not able to capture racial and ethnic disparities given the homogenous demographic of the study population.…”
mentioning
confidence: 99%
“…Not surprisingly, uninsured and Medicaid payor status were strong negative predictors for receipt of chemotherapy and/or surgery. A recent study demonstrated an increased probability of 1-year survival for patients diagnosed with and treated for pancreatic adenocarcinoma in Medicaid expansion states . However, socioeconomic and racial/ethnic disparities persisted.…”
mentioning
confidence: 99%